Mekanisme dan Akibat Hukum Terhadap Penundaan Kewajiban Pembayaran Utang (Studi Kasus Putusan Nomor 190/Pdt.Sus.PKPU/2022/PN.Niaga.Jkt.Pst dan Putusan Nomor 759/K/Pdt.Sus/2012) - Danindra Zachrie; Yesaya Geraldo Tambunan; Najwa Vira Nabila; Syachlan Maulana; Adhito Martogi Siregar (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Postponement of Debt Payment Obligations (PKPU) is a tool provided by law for debtors to avoid bankruptcy. In practice, PKPU can run well or vice versa. If PKPU can run well, the debtor will avoid bankruptcy, but if PKPU cannot run well, then the debtor will be declared bankrupt. This research aims to determine the mechanism for postponing debt payment obligations and the legal consequences of the peace agreement in PKPU and the rejection of the peace plan in PKPU. The research method used is normative juridical with a statutory approach and a case approach. From this research it can be concluded that the PKPU mechanism in Decision Number 190/Pdt.Sus.PKPU/2022/PN.Niaga.Jkt.Pst and Decision Number 759/K/Pdt.Sus/2012 starts from a PKPU application by the debtor or creditor, temporary PKPU decision, and permanent PKPU decision. The legal consequences arising from the peace agreement in PKPU are punishing the parties, both debtors and creditors, to submit and comply with and implement the contents of the Peace Agreement. Meanwhile, the legal consequences arising from the rejection of the peace plan in the PKPU are that the debtor is declared bankrupt.